KNH2 - KH: a metal amide - hydride solid solution - Santoru, Antonio (2016)
We report for the first time the formation of a metal amide-hydride solid solution. The dissolution of KH into KNH2 leads to an anionic substitution, which decreases the interaction among NH2 - ions. The rotational properties of the high temperature polymorphs of KNH2 are thereby retained down to room temperature.